Sedation for children undergoing painful prcedures: A randomized single blind trial comparing oral ketamine to intravenous morphine. - Awale, Pankaj (2006)
ABSTRACT: Background:The management of pain and anxiety in pediatric patients undergoing painful procedures is challenging. Objective:To compare and evaluate the effectiveness of oral ketamine with intravenous morphine in children undergoing painful procedures. Design & Methodology :This is a Prospective randomized single blind trial, conducted at Tansen Mission Hospital for the period of three months. Oral Ketamine group received IV preparation of Ketamine mixed with fruit juice at the dose of 8 mg/kg and IV morphine was given at the dose of 0.1 mg/kg. Statistical analysis was done with SPSS 13.0 Results:24 patients were referred 62 times by the surgeons for the purpose of the study. 60 patients (30 in each group) completed the study. Almost similar painful procedure were performed in each group (p=0.783). 24 (80%) of the patients had inadequate sedation in oral morphine group (p<0.001). SBP and DBP both were significantly higher in the oral ketamine group during the procedure compared with the baseline (p=0.016 & 0.035 resp.) but the MAP & Pulse rate was not raised significantly (p>0.05), whereas SPO2 was significantly lower in the IV morphine group (p=0.031).Adverse effects after administration of the drug was not different in both groups (p=0.436)expect the incidence of irrelevant talk was higher in oral ketamine group (p=0.005) and incidence of crying was higher in IV morphine group (0.002). Mean CHW Sedation scale and mean recovery time was significantly higher in oral ketamine (p<0.001 & =0.009 resp). Conclusions:In conclusion, this study showed that oral ketamine at the dose of 8 mg/kg had minimal side effects and was more effective but had a slower recovery than intravenous morphine at the dose of 0.1 mg/kg.